Laporan Penelitian Penyusunan Laporan Keuangan UMKM Berdasarkan SAK EMKM Pada Toko Kayla Di Kota Tanjungpinang Periode Agustus-Oktober 2024 - Rafika Okdanola Megarani; Aura Putri Januar; Surya Pratama Catri; Hadly Lidya Rikayana (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the rudimentary financial recording practices and the process of preparing financial statements for the Micro, Small, and Medium Enterprise (MSME) Toko Kayla in Tanjungpinang City. Toko Kayla, operating in the retail trade sector for daily necessities since early 2024, is an interesting object of research because despite having an active transaction volume, the owner, Ibu Muridawati, still records transactions simply and has not implemented the applicable accounting standards.The method used is quantitative descriptive with a case study approach, where data were obtained through interviews, observation, and documentation study of Toko Kayla's transactions and activities for the 2024 period. The research findings indicate that Toko Kayla's current financial records are not fully compliant with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). The lack of understanding regarding accounting and SAK EMKM is a major obstacle, making it difficult for the owner to accurately calculate profit or loss and resulting in a lack of formal financial reports (statement of comprehensive income, statement of financial position, and notes to the financial statements).